Rapid prototyping in the manufacture of 3D printed molds for plastic blowing - Carrillo, Gilberto; Nuila, Carolina; Laínez, jorge (INGENIUS Revista de Ciencia y Tecnología, 2020)
In the Salvadoran industry, we can find entrepreneurs and microentrepreneurs who do not have the resources to make plastic bottles with stylized designs that differentiate them from other brands and products, which prevents them from escalating to other market segments or international markets, slows the growth of their business. One possible cause is that the manufacture of blow molds requires a very expensive initial investment. However, there are alternatives such as the manufacture of low-run molds, which have lower resolution and shorter life time, but, at the same time, offer as a benefit a lower manufacturing cost and, therefore, lower acquisition cost for the entrepreneur, opening in this way the opportunity to be able to produce stylized bottles at convenience. Among the various ways to manufacture low-run molds, there is the reverse engineering technique, which requires rapid prototyping equipment. This article describes the reverse engineering procedure to generate the mold for blowing. With the available design the necessary mold was printed and with this, the bottles were manufactured, which were scanned to verify with computer program their dimensions comparing them against the original mold file. Simultaneously, the containers were verified in the industrial metrology laboratory to validate the computer results, these results are presented in the document.
Keywords: Molde para soplado; Impresión 3D; Creación rápida de prototipos; Botellas de plástico